Chang-rodríguez, Raquel (ed.). Franqueando fronteras: Garcilaso de la Vega y «La Florida del Inca». Lima: Pontificia Universidad Católica del Perú, 2006, 289 pp., ilustr. - Domínguez Faura, Nicanor (2009)
La reseña no tiene resumen.